Analisis Pelayanan Nasabah dalam Meningkatkan Kepuasan Pelanggan Pada Bank CIMB Niaga - Aldrich Azka Rama Athaariq; Tarangga Ali Ramadhani; Achmad Maulana Setia Putra; Ida Ayu Nuh Kartini (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Customer service is one of the important factors in the banking industry because it is directly related to customers. Good service quality can provide comfort and support customer satisfaction. This study aims to analyze customer service in improving customer satisfaction at CIMB Niaga Bank. The research employed a descriptive qualitative method with data collection techniques consisting of observation, documentation, and literature study. The observation was conducted by a group of three researchers. The results indicate that the services provided by CIMB Niaga Bank have been implemented quite well. This can be seen from the availability of teller and customer service facilities, an organized queue system, comfortable waiting areas, and friendly employees. In addition, digital banking services and ATM facilities help customers perform transactions more easily. Based on the observations, the quality of service provided has the potential to improve customer satisfaction by offering convenience and comfort in accessing banking services.